Core technology competencies for librarians and library staff : a LITA guide - Thompson, Susan M. (New York : Neal-Schuman Publishers, 2009)
Core Technology Competencies for Librarians and Library Staff provides a practical look at the skills, technological know-how, and personal attributes that enable librarians and staff to take full advantage of technology to deliver dynamic library collections and services.
Includes bibliographical references and index.
rua 02/12/13
Loans
Keywords: Librarians; Library employees; Technological literacy; Librarians; Library employees; Library education; Information technology; Core competencies